Student teachers' reading habits and preferences - Nana Priajana (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2013)
This study investigates the reading habit and preferences of the Student Teachers studying in their first year at the graduate school in Malang. Although with the advance of technology, media and many factors influencing reading habits and their preferences, the subjects of the study still have good reading habit and positive attitude towards reading activities. To collect the data, the researcher employs the questionnaire with 40 items adapted from a similar research. The items were designed for evaluating reading habits, general attitudes towards reading, and reading preferences of the students. As a result of the study, it is shown that more than half of the students like reading in leisure time and consider it as indispensable part of their lives.